Novel 3D Lung Tumor Spheroids for Oncoimmunological Assays. Issue 4 (23rd December 2021) - De Ridder, Kirsten; Tung, Navpreet; Werle, Jan-Timon; Karpf, Léa; Awad, Robin Maximilian; Bernier, Annie; Ceuppens, Hannelore; Salmon, Hélène; Goyvaerts, Cleo
Abstract : Lung cancer thrives in a complex multicellular tumor microenvironment (TME) that impacts tumor growth, metastasis, response, and resistance to therapy. While orthotopic murine lung cancer models can partly recapitulate this complexity, they do not resonate with high‐throughput immunotherapeutic drug screening assays. To address the current need for relevant and easy‐to‐use lung tumor models, a protocol is established to generate and evaluate fully histocompatible murine and human lung tumor spheroids, generated by coculturing lung fibroblasts with tumor cells in ultralow adherence 96‐well plates. A spheroid generation protocol with the murine Kras G12D p53 −/− (KP) and Lewis Lung Carcinoma (LLC) cell lines is delivered next to the human lung H1650 adenocarcinoma line. In addition, their application potential to study tumor‐stroma organization, T‐cell motility, and infiltration as well as distinct macrophage subsets' behavior using confocal microscopy is described. Finally, a 3D target‐specific T‐cell killing assay that allows spatiotemporal assessment of different tumor to T‐cell ratios and immune checkpoint blockade regimens using flow cytometry and live cell imaging is described. This 3D lung tumor spheroid platform can serve as a blueprint for other solid cancer types to comply with the need for straightforward murine and human oncoimmunology assays. Abstract : An easy‐to‐use murine and human 3D lung tumor spheroid platform in 96‐well format for gene, cell, and drug screening is reported. Importantly, this platform recapitulates the characteristic tumor islet in stroma architecture found in human lung cancer. Furthermore, it is suitable for macrophage and T‐cell infiltration studies as well as target tumor cell‐specific killing evaluation.